Standardisation and acceptability of dairy products with Cocoa Mass - Sunita Nair (Department of Home Science, College of Horticulture, 2002)
Standardisation and acceptability of dairy products namely milk chocolate, burfi, fudge, biscuits and ice cream were conducted by incorporating cocoa mass at 5 per cent and 10 per cent levels. The cocoa beans were roasted for 5 minutes and 10 minutes Shelf life of cocoa mass for three months was also assessed under ambient conditions. The results of the study indicated that the cocoa mass which was initially a powder got clumped by the third month and was insoluble in warm water. -The microbial count and peroxide values in cocoa mass increased gradually for both 5 minutes and 10 minutes roasting and recorded highest during the third month. Comparatively cocoa mass made by 10 minutes roasting had significantly low microbial count and peroxide value. The sensory evaluation of milk chocolate showed the products incorporated with cocoa mass at 5 per cent level were more acceptable. Ten per cent level was acceptable if the cocoa beans were roasted for 5 minutes The sensory evaluation of burfi showed 5 per cent level of incorporation of cocoa mass to be more acceptable. Five per cent level and roasted for 5 minutes were found to have optimum scores. Ten minute roasting with 10 per cent incorporation of cocoa mass made the product bitter and flowy. The sensory evaluation of fudge showed that there was a significant decrease in the Period mean of acceptability of texture and taste of fudge by the